Estrechamiento bilateral peruano-británico en el sector infraestructura en el Perú entre 2017 y 2021 - Herrada Ruiz, Alvaro Alejandro (Pontificia Universidad Católica del Perú, 2024)
This article seeks to explain the reasons why Peru and the United Kingdom tightened their bilateral relationship in the infrastructure sector between 2017 and 2021. Therefore, it is proposed that the bilateral relationship became closer since the first G2G contract for Lima 2019 was signed due to factors at the Peruvian and British State level. On the one hand, the Brexit referendum, and the process of the United Kingdom’s exit from the European Union, meant the need to promote the export of British goods and services internationally. In this sense, in Peru, the British identified an opportunity to attract the import of their expertise in the infrastructure sector. On the other hand, on the Peruvian side, it is proposed that the infrastructure gap in the country has been a pending issue on the public agenda. It is concluded that the bilateral relationship became closer in the infrastructure sector, because the British needed to improve their positioning in Peru after Brexit and that coincided with the visibility of the infrastructure problems faced by Peru, which generated the conditions for the narrowing of the gap.

Este artículo explica las razones por las Perú y Reino Unido estrecharon su relación bilateral en el sector de infraestructura entre 2017 y 2021. Por ello, se plantea que la relación bilateral se estrechó desde la firma del primer contrato G2G para Lima 2019 a partir de factores a nivel del Estado peruano y británico. Por un lado, la votación del Brexit, proceso de salida del Reino Unido de la Unión Europea, significó la necesidad de promover la exportación de los bienes y servicios británicos a nivel internacional. En este sentido, en el Perú los británicos identificaron una oportunidad para atraer la importación de su experticia en el sector infraestructura. Por otro lado, respecto al lado peruano, se propone que la brecha de infraestructura en el país ha sido un asunto pendiente en la agenda pública. Se concluye que la relación bilateral se estrechó en el sector infraestructura, porque existió una necesidad de los británicos de mejorar su posicionamiento en el Perú a partir del Brexit y que coincidió con la visibilización de los problemas de infraestructura que enfrentó el Perú que generaron las condiciones para el estrechamiento.
Peruvian-British bilateral tightening in the infrastructure sector in Peru between 2017 and 2021
Keywords: Infrastructure; Bilateral relations; Peru; United Kingdom; Government to Government (G2G); Infraestructura; Relaciones bilaterales; Perú; Reino Unido; Gobierno a Gobierno (G2G); https://purl.org/pe-repo/ocde/ford#5.09.01